THE ANALYSIS OF POLITENESS IN HARRY POTTER CHAPTER 1 MOVIE - Setyawati, Anisa; Rahayu, Silpia (IKIP Siliwangi, 2020)
Nowadays, movie is a media which has a biggest impact for the people. With movie people can learn about language. Language is procedure by human for communication with other people. Pragmatics is the strategies to analyze what the purposes of the utterance understanding, in pragmatics there have politeness to known how people express their negative and positive face. When people approximately impressive that threatens an additional face, it is shows how a face threatening act’s (FTA’s). When people talk with the other they apply positive and negative face in communication to save threatening acts. This article examines is how the analysis of politeness in Harry Potter Chapter 1 Movie. The author tries to analyze negative face, positive face on dialogue in this movie. Politeness strategies can be finds from face threat and how the speakers produce the words and gesture to communicate between actor in the characters. This research is observes by the author, because the subject on this research are movie to known how the actor and actress used their face in the dialogue of it. The result in this research aims it is essential for language learners study about politeness principles in instruction to increase a good communication.Keywords: Face Threatening Act’s, Negative and Positive Face, Movie, Politeness.